The SPACE Program: I. The featureless spectrum of HD 86226 c challenges sub-Neptune atmosphere trends - Kahle, Kim Angelique; Blecic, Jasmina; Ashtari, Reza; Kreidberg, Laura; Kawashima, Yui; Cubillos, Patricio E.; Deming, Drake; Jenkins, James S.; Mollière, Paul Maurice; Redfield, Seth; Tian, Qiushi Chris; Vines, Jose I.; et al. (Astronomy and astrophysics, 2025)
Sub-Neptune exoplanets are the most abundant type of planet known today. As they do not have a Solar System counterpart, many open questions exist about their composition and formation. Previous spectroscopic studies have ruled out aerosol-free hydrogen-helium dominated atmospheres for many characterized sub-Neptunes but are inconclusive about their exact atmospheric compositions. Here we characterize the hot (T eq =1311 K) sub-Neptune HD 86226 c (R=2.2 R⊕, M=7.25 M⊕), which orbits its G-type host star on a four-day orbit. The planet is located in a special part of the sub-Neptune parameter space: Its high equilibrium temperature prohibits methane-based haze formation, increasing the chances for a clear atmosphere on this planet. We used Hubble Space Telescope data taken with WFC3 and STIS from the Sub-Neptune Planetary Atmosphere Characterization Experiment (SPACE) Program to perform near-infrared (1.1-1.7 μm) transmission spectroscopy and ultraviolet characterization of the host star. We report a featureless transmission spectrum that is consistent within 0.4 σ with a constant transit depth of 418 ± 14 ppm. The amplitude of this spectrum is only 0.01 scale heights for a H/He-dominated atmosphere, excluding a cloud-free solar-metallicity atmosphere on HD 86226 c with a confidence of 6.5 σ. Based on an atmospheric retrieval analysis and forward models of cloud and haze formation, we find that the featureless spectrum could be due to metal enrichment [M/H] > 2.3 (3 σ confidence lower limit) of a cloudless atmosphere, or silicate (MgSiO3), iron (Fe), or manganese sulfide (MnS) clouds. For these species, we performed a detailed investigation of cloud formation in high metallicity, high-temperature atmospheres. Our results highlight that HD 86226 c does not follow the aerosol trend of sub-Neptunes found by previous studies. Follow-up observations with the James Webb Space Telescope could determine whether this planet aligns with the recent detections of metal-enriched atmospheres or if it harbors a cloud species that is otherwise atypical for sub-Neptunes.
Gesehen am 20.01.2026